THE EVALUATING MACHINE SAFETY AND SUSTAINABILITY BY CIRCULAR DESIGN: A COMPOSITE INDICATOR - Agusti, Febrina; Buwono, Ringgi Ismoyo; Dwyanton, Fertilio; Novianto, Damara Jibran (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Circular design offers significant potential for creating more environmentally friendly and sustainable machines. However, its implementation also presents a number of challenges, particularly related to operational safety and sustainability evaluation. A comprehensive evaluation approach and clear technical standards are needed to ensure that circularly designed machines remain efficient, safe, and suitable for long-term use. This research method uses a literature review to develop indicators. The results of this article identify 16 indicators that can be used to develop sustainable machine designs. These indicators are divided into two main categories: 8 indicators related to environmental aspects, including energy savings, recycling, reuse, toxic and hazardous materials, number of components, product durability, and environmentally friendly components; and 9 indicators related to technical aspects, including assembly and disassembly, product dimensions, product weight, maintenance, safety of use, ease of operation, ease of cleaning, ease of production, and product adaptability. Furthermore, indicator validation is crucial to ensure that the indicators used are relevant, accurate, and reliable in the context of developing sustainable machine designs.